1973
DOI: 10.1084/jem.137.3.660
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator of Cellular Immunity

Abstract: Bacterial parasites that can survive and multiply intracellularly are notable for their ability to induce delayed-type hypersensitivity and a concomitant state of resistance that is expressed in the enhanced capacity of macrophages to kill ingested organisms (1). The mechanism by which macrophages become activated in this respect has not been determined, but the process clearly involves an activity of specifically sensitized lymphocytes. These are formed in the infected animal and can be detected by their abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1973
1973
1983
1983

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 24 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…This agrees with published findings on the vinblastine sensitivity of the mediators of anti-Listeria immunity in the rat (12). The conclusion that they are rapidly dividing cells is reinforced by the additional finding that an increase in their numbers in the spleen is associated with a major increase in DNA synthesis.…”
Section: Discussionsupporting
confidence: 82%
“…This agrees with published findings on the vinblastine sensitivity of the mediators of anti-Listeria immunity in the rat (12). The conclusion that they are rapidly dividing cells is reinforced by the additional finding that an increase in their numbers in the spleen is associated with a major increase in DNA synthesis.…”
Section: Discussionsupporting
confidence: 82%
“…Since small lymphocytes generated in the "rest" interval after the last injection of [3H]thymidine would not be expected to be labeled, it could be argued that newly formed small lymphocytes or possibly a subset of "short-lived" cells have an exudate-seeking capacity similar to that demonstrated for immunoblasts. This possibility cannot be discounted; for when rats with induced peritoneal exudates are transfused with TDL obtained from donors given a course of [3H]thymidine injections immediately before incannulation, labeled small lymphocytes, in addition to immunoblasts, are found later in the exudates (2). While some of these labeled small lymphocytes may have derived from exudate-seeking immunoblasts that escaped the inhibiting influence of vinblastine, others may have emigrated from the blood in a fully differentiated condition.…”
Section: Discussionmentioning
confidence: 98%
“…Studies using autoradiographic techniques have shown that after intravenous injection, labeled immunoblasts from the thoracic duct lymph of donor rats accumulate in substantial numbers in peritoneal exudates induced by killed bacteria (2,8). The exudate-seeking cells give rise by cell division and cell differentiation to a population of more lightly labeled small lymphocytes.…”
Section: Effect Of Vinblastine On the Protective Capacity Of Pec--mentioning
confidence: 99%
See 2 more Smart Citations